Classroom Teachers’ Efforts to Overcome Mathematics Learning Difficulties (Dyscalculia) in Elementary School Students - Rafikatul Rafika; Bella Helliyana Febria; Moh. Ainor Rofiqi (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
Learning difficulties in mathematics are a common problem experienced by elementary school students, particularly in basic arithmetic operations, which can impact their academic achievement and attitudes toward mathematics in the future. This study aims to examine teachers’ efforts in overcoming mathematics learning difficulties among elementary school students, especially those experiencing dyscalculia. The research employed a qualitative approach using a case study method at SDN Gunggung 1, with the fifth-grade homeroom teacher selected as the research subject through purposive sampling. Data were collected through in-depth interviews and analyzed using descriptive qualitative analysis techniques. The results of the study indicate that fifth-grade students experience difficulties in mathematics, particularly in multiplication and division operations. These difficulties are caused by low learning motivation, limited parental supervision due to work commitments, and dependence on technology that reduces the habit of memorizing basic concepts. The teacher’s efforts to address these challenges include strengthening multiplication memorization, implementing heterogeneous group learning, and maintaining communication with parents through home visits. This study concludes that successfully overcoming mathematics learning difficulties requires effective collaboration between teachers, schools, and parents to ensure optimal learning continuity.